Temporal and Spatial Variability of the CO2 System in a Riverine Influenced Area of the Mediterranean Sea, the Northern Adriatic - Urbini, Lidia; Ingrosso, Gianmarco; Djakovac, Tamara; Piacentino, Salvatore; Giani, Michele (Frontiers in Marine Science, 2020)
Coastal ecosystems are subject to multiple processes that drive pH change over time. Therefore, efforts to understand the variability in the coastal carbonate system are crucial to assess the marine system vulnerability to acidification. The variations of the carbon dioxide (CO2) system were studied, from December 2014 to January 2017, on 6 stations along a transect latitudinally crossing the northern Adriatic, from the Po River delta to the Istra Peninsula. The study aims to evaluate the influence of riverine inputs and other environmental drivers, such as temperature, air-sea CO2 exchanges and biological processes, on the carbonate system. Riverine discharges significantly affected the carbonate system, as they are an input of total alkalinity and nutrients. High alkalinity concentrations were measured in low salinity waters and a significant negative correlation between salinity and alkalinity was found. The influence of biological processes was underscored by the significant inverse correlation between pHT at a constant temperature (pHT25°C) and apparent oxygen utilization, and by the positive correlation between chlorophyll a and pHT25°C in samplings close to flood events. Moreover, thermic and non-thermic partial pressure (p) of CO2 in surface waters was evaluated. pCO2 was more strongly influenced by the thermal effect during summer, while the biological effect prevailed in the other seasons. The analysis of air-sea CO2 fluxes highlighted that the area acts as a sink of CO2 during winter, spring and autumn and as a source during summer. A biogeochemical simulation was used for bottom and surface waters to estimate future changes in northern Adriatic carbonate chemistry with the increase of anthropogenic CO2 and temperature, and to understand how biological processes could affect the expected trends. By 2100, under the IPCC scenario of business as usual and without the effect of biological processes, pHT is expected to decrease by ~0.3 and the aragonite saturation is expected to decline by ~1.3, yet not reach undersaturation values. Even though the northern Adriatic is characterized by high alkalinity buffering, pH seasonal variability will likely be more pronounced, due to the strong decoupling of production and respiration processes driven by stratification of the water column.